Innovation barriers amongst clusters of European SMEs. (1st January 2002) - Pihkala, Timo; Ylinenpaa, Hakan; Vesalainen, Jukka
Research on innovations and barriers to innovation has for a long time been concentrated on trying to find those mechanisms that would help in designing innovation-supporting policies at European, national and company level. Often, these studies have, however, been looking at only one of the levels at a time, which has led to oversimplifications and misleading policy implications. This paper stems from the need to know more about how the innovativeness of smaller firms is related to contextual factors. The innovation process is seen as a cycle involving trial and error, where problems at some stages of development lead to a need to re-evaluate earlier stages in the innovation process. The barriers to innovation are not, however, the same for each firm; barriers may be expected to differ, for example, according to the size of the firm, the line of industry, and the degree of innovativeness of the firm. This study aims to show that there are distinct categories of firms behaving differently vis-a-vis barriers to innovation. The data includes survey responses from 1, 240 firms from four European countries Belgium, Finland, Ireland and Sweden. In the analysis, eight factors causing innovation barriers emerged: employment policy, financing, taxation, legislation, risk-propensity, competence and information, and external support. The findings suggest that the barriers to innovation should be studies from the decision-makers point of view. In further analysis, eight clusters were identified: high innovation firms with market competition barriers, exogenous low innovative firms, low-innovation firms with competence and information barriers, high and low innovation firms with no barriers to innovation, medium innovative manufacturing firms, low-innovation service firms with employment policy barriers, medium innovation firms with financial barriers and low-innovation craftsmen and service firms. The study concludes that the inter-relation between different sets of barriers to innovation seems to hold more importance than has been recognised previously. Moreover, the barriers to innovation are not equally distributed among SMEs, but there are typical sets of barriers to innovation depending on the age, size, type of industry, and the innovativeness of the firm. As for policy implications, the study suggests that more attention should be paid to lowering or removing barriers that in particular obstruct medium-innovative firms from innovating.